2019
DOI: 10.2174/1389450119666180803121737
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib in Cancer Therapy and Prevention – Review

Abstract: Both preclinical and clinical studies have demonstrated promising results of the role of celecoxib in the treatment and prevention of cancer - the best outcome was observed in colon, breast, prostate and head and neck cancers. However, more clinical trials providing real evidence-based clinical advances of celecoxib use are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 115 publications
2
94
0
Order By: Relevance
“…Various mechanisms of the anticancer potential of celecoxib have been indicated in the available literature. Many authors suggest that it is not only the inhibition of COX-2 but the regulation of other factors involved in the development of malignant tumours by the drug that has a considerable impact on hindering tumour growth (i.e., a decrease in OCT4, SOX2, and BMP7 gene expression, increase in the expression of E-cadherin gene, Wnt/β-catenin, cell adhesion molecules, and surface receptors: AMFR and EGFR, induction of p53 gene expression) [39]. However, no evidence of the drug's effect on PRODH/POX activity has been demonstrated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms of the anticancer potential of celecoxib have been indicated in the available literature. Many authors suggest that it is not only the inhibition of COX-2 but the regulation of other factors involved in the development of malignant tumours by the drug that has a considerable impact on hindering tumour growth (i.e., a decrease in OCT4, SOX2, and BMP7 gene expression, increase in the expression of E-cadherin gene, Wnt/β-catenin, cell adhesion molecules, and surface receptors: AMFR and EGFR, induction of p53 gene expression) [39]. However, no evidence of the drug's effect on PRODH/POX activity has been demonstrated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another group revealed that COX inhibitors could effectively upregulate the production of CXCL9 in ovarian and breast cancers since PGE 2 , a downstream product of COX, negatively regulates CXCL9 expression . Focusing on COX inhibitors should be appealing because it has been well recognized as a useful candidate for repositioning drugs in treating and preventing cancers . Furthermore, overexpression of COX, especially COX‐2 isoform, is deemed oncogenic; it has contributed to immune evasion in many types of cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The COX2 selective inhibitor celecoxib alone and in combination with BRAF/MEKi has shown tumor inhibitory effects in preclinical melanoma studies [ 44 , 45 ]. Clinical trials have also reported the effect of COX2 inhibitors, alone or combined with other treatment modalities, in cancer patients [ 17 , 18 ]. However, there are no clinical reports investigating the treatment effect of COX2 inhibitors on BRAF/MEKi melanoma resistance.…”
Section: Discussionmentioning
confidence: 99%
“…While COX1 is constitutively expressed, COX2 is induced by different factors, such as growth factors and proinflammatory cytokines, including CCL2. Celecoxib is a nonsteroidal anti-inflammatory drug that specifically inhibits COX2, commonly used for the treatment of rheumatoid arthritis [ 18 ]. This drug is currently being repurposed in a clinical trial evaluating its treatment and prevention of cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%